Changes in the clustering of unhealthy movement behaviors during the COVID-19 quarantine and the association with mental health indicators among Brazilian adults - Werneck, André O. (2020)
University of São Paulo. Department of Nutrition, School of Public Health. São Paulo, SP, Brazil.